2009
DOI: 10.1186/1471-2407-9-26
|View full text |Cite
|
Sign up to set email alerts
|

Human Papillomavirus (HPV) in breast tumors: prevalence in a group of Mexican patients

Abstract: BackgroundBreast cancer is one of the main health problems in developed countries, occupying first place in mortality in women. It is well-known that there are risk factors associated with breast cancer development. Nonetheless, in 50–80% of cases known risk factors have not been identified, this has generated the attempt to identify new factors related with this neoplasia as viral infections. The aim of this work is investigate the prevalence of HPV DNA in patients with breast lesions at the Instituto Naciona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
42
2
4

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(57 citation statements)
references
References 16 publications
9
42
2
4
Order By: Relevance
“…In this study, the presence of HPV was detected in 63.6% of breast cancer samples, while only 4.5% of benign pathology tissue biopsies were positive for this virus. This detection frequency is within the previously published worldwide range, with a prevalence ranging from 10-86% 4,5,14,16,[29][30][31][32] , where the works by Akil, et al 4 in 2008 and Antonsson, et al 30 in 2011 detected 61.06 and 50% of HPV DNA-positive cases by means of multiplex PCR and assembly PCR, respectively.…”
Section: Discussionsupporting
confidence: 84%
“…In this study, the presence of HPV was detected in 63.6% of breast cancer samples, while only 4.5% of benign pathology tissue biopsies were positive for this virus. This detection frequency is within the previously published worldwide range, with a prevalence ranging from 10-86% 4,5,14,16,[29][30][31][32] , where the works by Akil, et al 4 in 2008 and Antonsson, et al 30 in 2011 detected 61.06 and 50% of HPV DNA-positive cases by means of multiplex PCR and assembly PCR, respectively.…”
Section: Discussionsupporting
confidence: 84%
“…Another definitive method to detect molecular contamination is the comparison of sequences of experimental samples with those of positive controls. Some researchers sequenced the amplifications obtained in the PCR reactions, but they did not provide enough details to judge the quality of the sequencing procedure [49, 51, 53, 61, 63, 64]. …”
Section: Causes Of False-positive Resultsmentioning
confidence: 99%
“…Most studies employed an initial PCR amplification using the standard commercially available primers used to screen HPV in cervical tissue [41, 42, 44, 47, 50-52, 54, 55, 57-61, 63, 65, 66, 69, 73, 76, 77, 80, 81]. These primer sets, like GP, MY, SPF, are within the L1 region, which codes most of the proteins in the viral capsid, and they more accurately detect the best known genital and/or oncogenic HPV types, i.e., HPV 6, 11 , 16, 18, 31, 33, 35, 39, 40, 42, 45, and 51–59.…”
Section: Resultsmentioning
confidence: 99%
“…De León et al (2009) (23) found 29% (15/51) of HPV DNA by PCR in breast carcinomas within an average age of 53 years and average tumor size of 9 cm, of which ten of the cases (66,6%) were positive to HPV-16, three (20%) to HPV-18, and two cases (13,4%) positive to both of them. In the benign conditions group (43 cases), all were negative to HPV-DNA.…”
Section: The Possible Involvement Of Hpv In Breast Cancermentioning
confidence: 99%
“…Damin tissue. In some studies, high-risk HPV was detected in normal tissue and in low levels of cancer (19,23,25,27,29,30,33) . The definition of normal tissue is important, as non-malignant areas can contain atypia with high-risk of cancer recorrence.…”
Section: The Possible Involvement Of Hpv In Breast Cancermentioning
confidence: 99%